Dopamine and glucose, obesity, and reward deficiency syndrome - Blum, Kenneth; Thanos, Panayotis K.; Gold, Mark S. (Frontiers in Psychology, 2014)
Obesity and many well described eating disorders are accurately considered a global epidemic. The consequences of Reward Deficiency Syndrome, a genetic and epigenetic phenomena that involves the interactions of powerful neurotransmitters, are impairments of brain reward circuitry, hypodopaminergic function and abnormal craving behavior. Numerous sound neurochemical and genetic studies provide strong evidence that food addiction is similar to psychoactive drug addiction. Important facts which could translate to potential therapeutic targets espoused in this review include: 1) brain dopamine (DA) production and use is stimulated by consumption of alcohol in large quantities or carbohydrates bingeing; 2) in the mesolimbic system the enkephalinergic neurons are in close proximity, to glucose receptors; 3) highly concentrated glucose activates the calcium channel to stimulate dopamine release from P12 cells; 4) blood glucose and cerebrospinal fluid concentrations of homovanillic acid, the dopamine metabolite, are significantly correlated and 5) 2-deoxyglucose the glucose analogue, in pharmacological doses associates with enhanced dopamine turnover and causes acute glucoprivation. Evidence from animal studies and human fMRI support the hypothesis that multiple, but similar brain circuits are disrupted in obesity and drug dependence and DA-modulated reward circuits are involved in pathologic eating behaviors. Treatment for addiction to glucose and drugs alike, based on a consensus of neuroscience research, should incorporate dopamine agonist therapy, in contrast to current theories and practices that use dopamine antagonists. Until now, powerful dopamine-D2 agonists have failed clinically, due to chronic down regulation of D2 receptors instead, consideration of novel less powerful D2 agonists that up-regulate D2 receptors seems prudent. We encourage new strategies targeted at improving DA function in the treatment and prevention of obesity a subtype of reward deficiency.